(untitled) (Research, Society and Development, 2020)
This study aims to analyze in the literature the association of awake and sleep bruxism with anxiety. An integrative literature review was conducted with articles published between 2015 and 2020 in the online databases PubMed (National Libary of Medicine) and Embase, using the descriptors organized in Boolean logic in accordance with two semantic fields: "Bruxism AND Anxiety", following the steps: identification of the works, screening, eligibility and inclusion. Cross-sectional clinical observational studies, randomized clinical studies and longitudinal studies were included when addressing the association of awake and sleep bruxism with anxiety, or both. Among the 1000 articles found, only 13 were selected. In fact, some studies have reported a statistical association between awake and sleep bruxism and anxiety, as well as some specific symptoms of anxiety have shown an association with bruxism in adults. Thus, it can be concluded that there is a high number of statistical associations of bruxism with anxiety, although it cannot be affirmed which type of bruxism is most associated with this emotional state.